The Xmrk oncogene promoter is derived from a novel amplified locus of unusual organization. - Förnzler, D; Altschmied, J; Nanda, I; Kolb, R; Baudler, M; Schmid, M; Schartl, M (Genome Research, 1996)
Hereditary melanoma in Xiphophorus hybrids is caused by the receptor tyrosine kinase Xmrk. Tumor formation is initiated by overexpression of the Xmrk gene, apparently because of insufficient transcriptional control in the melanocytic lineage of hybrid fish. The oncogenic Xmrk resulted from gene duplication and nonhomologous recombination of the corresponding Xmrk proto-oncogene during evolution. By this event Xmrk was translocated downstream of the promoter of another gene, D (for Donor). This raised the question whether both the Xmrk oncogene and D share similar transcriptional control elements. Studies on the genomic organization of D showed that this gene is amplified in the Xiphophorus genome, presumably with all copies clustered on a single chromosome. Surprisingly, at least two completely different, tightly linked genes are included in the amplified segment. We find a ubiquitously expressed zinc finger gene of the krüppel type, followed by a previously unknown gene, which was the partner of the Xmrk proto-oncogene in the recombination generating the Xmrk oncogene. The nucleotide sequence predicts a gene product with very high amino acid similarity to a hypothetical Caenorhabditis elegans protein. The expression pattern is unrelated to that of the Xmrk oncogene suggesting that despite extended sequence homology a new type of promoter was created by this rearrangement.